AN ALTERNATIVE MODEL FOR POSITIVE SHIFTS IN SHALLOW-MARINE CARBONATE δ13 C AND δ18 O - Immenhauser A.; Della Porta G.; Kenter J.A.M.; Bahamonde Ju.R. (My University, 2003)
Positive shifts in global seawater δ13 CDIC are related to changes in the ratio of organic relative to inorganic carbon burial in oceanic basins, whereas factors such as climatic cooling and the accumulation of polar ice are known to cause positive shifts in δ18 O. Here, an alternative model is proposed for the formation of local positive isotope shifts in shallow-marine settings. The model involves geochemically altered platform-top water masses and the effects of early meteoric diagenesis on carbonate isotopic composition. Both mechanisms are active on modern (sub)tropical carbonate platforms and result in low carbonate δ13 C and δ18 O relative to typical oceanic values. During high-amplitude transgressive events, the impact of isotopically light meteoric fluids on the carbonate geochemistry is much reduced, and 13 C-depleted platform-top water mixes with open oceanic water masses having higher isotope values. Both factors are recorded as a transient increase in carbonate 13 C and 18 O relative to low background values. These processes must be taken into consideration when interpreting the geochemical record of ancient epeiric seas.
Keywords: CARBONATES; CARBONIFEROUS; DIAGENESIS; EPEIRIC SEAS; ISOTOPES; PALAEOCEANOGRAPHY; Paleozoic::Carboniferous; Палеозой::Каменноугольная